Thoron, the living storm - Blade, Adam (Blade, Adam. Beast quest, 2016)
Tom and Elenna have tracked down Emperor Jeng and the evil witch Kensa while searching for the second weather-controlling crystal, but Thoron is unlike any beast they've faced before.